Enterprise Architecture Challenges and Opportunities in Higher Education Institutions: A Case Study from Saudi Arabia - Hassan ALGHAMDI (Communications of International Proceedings, 2024)
Enterprise Architecture (EA) practices are accepted worldwide to enable digital transformation and deal with the complexity of business and IT alignment in socio-technical organizations. It is a growing trend, and research efforts are devoted to facilitating its effective adoption in public and private organizations. However, little EA research has focused on its implementation in the higher education sector. This interpretive case study paper highlights the challenges Al-Baha University -a higher education institution from Saudi Arabia- faced while developing its EA. Al-Baha University is the first Saudi university to develop its EA according to the standards and regulations of the Digital Government Authority in Saudi Arabia. Solutions and recommendations to overcome these challenges are presented to provide insights to local and international universities on how they can deal with the challenges associated with EA implementations in this sector. These insights would also assist other organizations to ensure more effective and sustainable digital transformation journeys from an EA perspective.
Keywords: enterprise architecture; digital transformation; higher education